1977
DOI: 10.1126/science.557841
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Modulation of the Immune Response

Abstract: After mice were exposed to a daily auditory stressor for varying lengths of time, the responses of their splenic lymphoid cells in vitro were assessed. Both the blastogenic activity of concanavalin A or lipopolysaccharide and the ability of immune lymphocytes to lyse P815 target cells showed the same patterns of immunosuppression and enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
3
4

Year Published

1979
1979
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(124 citation statements)
references
References 14 publications
5
112
3
4
Order By: Relevance
“…Various stress impact is commonly followed by a proliferation decrease (Monjan and Collector 1977, Hoffman-Goetz et al 1986, Odio et al 1986, Rabin and Salvin 1987. In our study the indications for a decrease of T-lymphocyte proliferation with ConA in the stressed animals and their progeny were found (Table 4).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Various stress impact is commonly followed by a proliferation decrease (Monjan and Collector 1977, Hoffman-Goetz et al 1986, Odio et al 1986, Rabin and Salvin 1987. In our study the indications for a decrease of T-lymphocyte proliferation with ConA in the stressed animals and their progeny were found (Table 4).…”
Section: Discussionsupporting
confidence: 56%
“…However, there are some data showing that a noise can lead to a decrease of B-cell proliferation with LPS (Monjan and Collector 1977). It has been found that various stress impact could lead to a suppression of B-cell activity and to a decrease in number of the antibody forming cells (Gisler 1974, Boranic et al 1984, Esterling and Rabin 1987, Keller et al 1988, Kirillina et al 1989.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key causal mechanisms of this relationship is thought to be the general catabolic influence of high circulating cortisol on certain muscle types and fat cells (Sapolsky et al, 2000;Yoshioka et al, 2005). Overall health indicators were also assessed, as chronic stress is known to have a generally suppressive effect on the immune system (Monjan and Collector, 1977;Jasnow et al, 2001;Kanitz et al, 2004). Again, this association is mediated, at least in part, by glucocorticoids (Chrousos, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In animals, acute exposure to electric shocks (Keller, Weiss, Schleifer, Miller, & Stein, 1983), social defeat (Fleshner, Laudenslager, Simons, & Maier, 1989; review by Bohus & Koolhaas, 1991), maternal separation (Coe, Rosenberg, & Levine, 1988;Laudenslager, Held, Boccia, Reite, & Cohen, 1990), rotation (Esterling & Rabin, 1987)), the odor of a stressed conspecific (Zalcman, Richter, & Anisman, 1989), immersion in cold water (Jiang, MorrowTesch, Beller, Levy, & Black, 1990), restraint (Bonneau, Sheridan, Feng, & Glaser, 1991a, 1991b, handling (Moynihan et al, 1990), intraperitoneal injection of saline (Moynihan, Koota, Brenner, Cohen, & Ader, 1989), and loud noise (Monjan & Collector, 1977) have all been shown to suppress some aspect of immunity. Chronic stressors such as crowding (Rabin, Lyte, Epstein, & Caggiula, 1987) have also been examined.…”
Section: Stress and Immunitymentioning
confidence: 99%